Soil compaction effects of rubber -wheel tractors and half -track tractors in rice cultivation - Mat Nasir, Radiah; Mat Su, Ahmad Suhaizi; Yahya, Azmi; Mat Nawi, Nazmi; Wagiman, Nurul Azimah (Malaysian Society of Agricultural Engineers, 2019)
As the machinery being operated in the field, the damage to the soil is obvious, which common damages appears mainly to the top soil layer such as increase in soil compaction and may create the ‘soft soil’ spot. However, the magnitude and the level of the damaged soil layer is challenging to quantify over the spatial distribution of the area. The study is focusing on comparing the level of soil compaction between rubber-wheeled tractor (RWT) and half-track tractor (HTT) during tillage operation using a rotovator implement in rice production. The widely used of HTT feared to cause damage to the soil hardpan as compared to common RWT type. A field study was conducted at Tunjang, Wilayah II – Jitra, Kedah with total area of 3.4 ha. More than 4000 data set of the soil pressured was measured using the soil penetrologger throughout two main growing seasons; wet and dry. The statistical analysis using T-test across all stages and operations revealed no significant different between the RTT and HTT on the soil compaction at the top soil layer (0-20 cm). However, the overall pressure from HTT is slightly higher than RWT, but below than threshold values of 1.4 MPa, thus may not limiting the root growth of the rice plant.